(untitled) (Journal of Pathology of Nepal, 2019)
Background: Conventional Cervical Cytology is the most widely used cervical cancer screening test. The incidence of cervical carcinoma is incredibly high in developing countries due to lack of proper knowledge. The extensive use of cervical screening with Papanicolau smears had considerably increased the detection of precancerous and cancerous lesion of uterine cervix. Study was conducted to evaluate cytohistological correlation and to calculate concordance and discordance of Pap smear in detection of precancerous and cancerous lesions of uterine cervix. Materials and Methods: A total of 54 samples reported in Pap smear as cervical intraepithelial lesions and suspicious for invasive malignancies were selected and correlated with corresponding histopathological findings. It was an observational study done for a period of 18 months from November 2016 to May 2018 at UCMS-TH. All the statistical evaluation was done by using SPSS version 20. Results: During the study period 54 cases were evaluated. Atypical Squamous Cell of Undetermined Significance was the common abnormal findings in the Pap smear with frequency of 26 (48.1%). Out of total 54 cases of Pap smears, 30 (55.55%) were concordant while discrepancies occurred in 24(44.44%) cases with cervical biopsy. Conclusions: The study revealed a good correlation between cervical cytology and cervical biopsy. We also concluded that conventional Pap smear is a cost effective test for the early detection of precancerous and cancerous cervical lesions.